INFORMATION TECHNOLOGIES IN THE EVALUATION ENVIRONMENT - HREHOVA, Stella; MACUROVA, Anna (Trends in education, 2010)
Destabilization of the ecosystem is defined by the name ecological stress. The methods of the formation and solution of algebraic equation systems by matrix are used in the solution destabilization of the ecosystem. Analysis of the selected environment elements can be performed by using information technologies and mathematical methods.
Keywords: ecosystem; environment; measure of the destabilization of the ecosystem.